The effect of country personality on destination choice and satisfaction - Akgoz, Erkan; Gok, Hatice Sari; Salvarci, Simge; Aylan, Kubra Celiloglu (Journal of Tourism Management Research, 2023)
The developments in the century we live in have also affected the tourism sector. In particular, competition between destinations has increased, and many new destinations have begun to be offered to tourists. This situation has caused the decision-making processes of tourists to become more complex. Because consumption preference decisions are affected by emotional as well as rational factors. Many factors play a role in tourists' destination choices and purchasing decisions. When we consider countries as destinations, country personalities can also influence the destination choice of tourists. From this point of view, it is aimed at determining whether the country’s personality as perceived by tourists visiting Turkey has an effect on their destination choice and satisfaction. It is known that a positive perception of country personality has a significant effect on consumers' destination choice and, accordingly, their satisfaction with the destination. In this context, first a conceptual framework was created, and then data were collected through face-to-face and online surveys with tourists. In the research, 395 of the questionnaires applied to foreign tourists visiting Turkey were evaluated. The data obtained in the study were analyzed with the SPSS statistical package program and discussed in terms of descriptive and inferential statistics. As a result of the analysis, it has been determined that there is a significant relationship between the country personality's destination choice and satisfaction. In addition, with the regression analysis, it was seen that the personality of the country positively affected both the destination choice decisions and satisfaction perceptions of the tourists.